Answer:
4
Step-by-step explanation:
-4+3=-1
-1+5=4
Step-by-step explanation:
hope it will be helpful to you
Answer:
x= -3 and y = 6
Step-by-step explanation:
so basically what you are trying to do is reduce into finding x and y
what you do is you want to find a number to multiply one of the equations in order to get the same x or y value does not matter which
so,...
we can do
either 20x or 15y
we will go with the smallest 15y
so for both equations multiply the whole thing by 5 for the first equation and by 3 for the second
5 x 5x+3y=3 --> 1
3 x 4x+5y=18 --> 2
we then get
25x+15y = 15 -->1
12x + 15y = 54 -->2
then now that you have the same Y values you can subtract ! which cancels out both the 15y
25x+15y = 15 -->1
- 12x + 15y = 54 -->2
13x =-39
so now x=-3 and all you have to do with x = -3 is sub this into either one of the equations that you started with !
x = -3
5(-3) +3y =3
-15 + 3y = 3
3y = 3+15
3y=18
y = 6!
7/12 u need to multiply 3*4 and u keep the numerator the same
Answer:
![y=4x^{3}](https://tex.z-dn.net/?f=y%3D4x%5E%7B3%7D)
Step-by-step explanation:
It is known that,
<em>'Vertical stretch, stretches the function up and down towards the y-axis'.</em>
The general form of vertical stretch is given by 'kf(x)', where k>1 is the factor by which function is stretched.
As, we have the function
which is stretched by a factor of 4.
Thus, the new function will be
.
Hence, the equation for the vertical stretch is
.